Pilkada Paslon Tunggal, Kinerja Partai Politik, dan Masa Depan Demokrasi di Indonesia - Arif Budiman (Jurnal Adhyasta Pemilu, 2018)
The number of single contestant within three occasion times of local election is continously rising. Besides, political parties are eligible to set the competition involving more than one contestant. This leads political parties performance comes into questions. Since many political scientists believed that quality of democracy depends on the degree of political parties’ performance, there have been inquires on how fine Indonesian democracy will be in the future. Through qualitative approach, descriptive methods, and literature review of collecting data technique, this research concludes that the rise of single contestants has negative impact on the political parties’ image and performance. Furthermore, while the quality of democracy is influenced by the political parties’ performance, the decrease on their image and performance consequently leads Indonesian democracy into negative path. Political parties-backed single contestant is conclusively a threat to the future of Indonesian democracy.